PSYCHOPOETICS: REFLECTING ON THE EXPERIENTIAL PERSPECTIVE OF INTERPRETING POETRY - Olga P. Vorobyova (Вісник університету ім. А. Нобеля. Серія Філологічні науки, 2023)
Current trends of poetic texts analysis, mainly due to interdisciplinarity of present-day philological studies, give impetus to the emergence of new varieties of linguipoetic studies. It fully concerns Psychopoetics as an area of research that addresses empirical and psychological foundations of the readers’ response to poetry in its experiential dimension. That is the way Psychopoetics is viewed by Prof. Willie van Peer and Anna Chesnokova in their book “Experiencing Poetry: A Guidebook to Psychopoetics” (London, etc.: Bloomsburry Academic, 2023). And that is exactly what made me start reflecting upon the issues brought up, their presentation, and upon research heuristics of the authors’ hypotheses. Such reflections aim to establish the place of Psychopoetics among other types of poetics, to define the heuristic potential of qualitative and quantitative techniques applied to poetry analysis as well as assess the contribution this discipline could make to elaborating the metamethod of interpreting poetry and, wider, literary text per se. Relying upon the method of introspection along with new gains in Cognitive and Multimodal Poetics, Intermediality studies and basic assumptions of the theory of emotional resonance makes it possible to correlate traditional and novel facets of poetological text analysis in a new light, while prognosticating the vectors of its further elaboration. The latter prove to fit in the global vector that characterizes the evolution of linguistic paradigms, i.e. from the emphasis upon structural and functional properties of text and its elements to focusing on dominant mental images and key concepts in their emotional and value-oriented aura, and still further to searching for sources and mechanisms of energy-driven impact pertaining to literariness and its poetic manifestations upon the reading audience. The same can be said about the impact of this book on the prospective audience, given its transparent structure, creative and up-to-date manner of presenting the material, and its authors’ undoubted love of poetry.